(untitled) (Marketing Journal, 2025)
Ensuring economic stability in the country is not only a matter of achieving sustainable growth rates, but also an important strategic task that ensures the continuous continuation of socio -economic development. This article analyzes the role of “driver” s ectors in achieving economic stability in the Republic of Uzbekistan — that is, sectors that act as the main driving force of the economy, their current state and future development prospects. In particular, the industry, information technology, agricultur e, logistics, energy and tourism sectors are considered as driver sectors, and each of them is evaluated based on the added value and new jobs created for the countryʼs economy, as well as its contribution to export potential. The article also deeply analy zes the factors that drive the development of driver sectors, in particular, state policy, investment environment, the state of introduction of innovative technologies, and the possibilities of effective use of foreign experience. Based on available statis tical data, the share of these sectors in GDP, their role in exports, and their role in meeting the demands of the domestic market are highlighted. The article concludes with the forecast results of achieving economic stability through driver industries an d recommendations for their implementation.